A comparison study of aggregate carbonation and concrete carbonation for the enhancement of recycled aggregate pervious concrete. (31st March 2023) - Tang, Bowen; Fan, Meng; Yang, Zhengquan; Sun, Yongshuai; Yuan, Linjuan
Graphical abstract: Highlights: Aggregate carbonation and concrete carbonation treatments with recycled aggregate pervious concrete were compared. The mechanisms of aggregate carbonation and concrete carbonation were investigated. The environmental benefits of aggregate carbonation and concrete carbonation were analysed. The concrete carbonation method is recommended for recycled aggregate pervious concrete. Abstract: Using recycled aggregates (RAs) to manufacture pervious concrete is one of the resource utilization methods of construction and demolition waste (C&DW). However, because of the poor quality of RAs, the mechanical strength of recycled aggregate pervious concrete (RAPC) is comparatively low, which limits its application to a certain extent. In this study, two types of carbonated recycled aggregate pervious concrete (CRAPC-I and CRAPC-II) were prepared by aggregate carbonation and concrete carbonation, respectively. First, the physical properties, such as the permeability, hardened density, porosity, and compressive strength, of CRAPC-I, CRAPC-II and recycled aggregate pervious concrete (RAPC) were measured. Second, the microstructure and mineralogical composition were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD) and thermogravimetric analysis (TGA). Besides, the strengthening mechanisms and environmental benefits of the CRAPC were analysed. The obtained results show that both aggregate carbonation and concrete carbonation can improve the compressive strength while ensuring acceptable permeability of pervious concrete, and concrete carbonation is more effective. Under the same carbonation conditions, concrete carbonation sequesters more CO2 than aggregate carbonation, which is more beneficial to the environment. This study may have the potential for the promotion and application of CRAPC.